Decadal trends in shark catches and effort from the New South Wales, Australia, Shark Meshing Program 1950-2010 - Reid, D.; Robbins, William; Peddemors, V. (2011)
The New South Wales (NSW) government has operated a program of netting beaches for the protection of swimmers and surfers against shark attack since 1937 in Sydney, and since 1949 in Newcastle and Wollongong. The scope and directives of the Shark Meshing Program have remained constant since its inception, with operational modifications in net specifications in 1972, changes in spatial deployment in 1972, 1987 and 1992, and the elimination of winter netting since 1989. This markedly increased meshing effort in 1972, and again in 1987. In the present study, we examine the trends in catch and effort for the period from 1950-1951 to 2009-2010 over this 200-km section of the NSW coast. Significant temporal trends in species, size and sex composition are described herein. Catches were consistently dominated by three shark taxa, hammerhead sharks (Sphyrna spp.), whaler sharks (Carcharhinus spp.) and Australian angel sharks (Squatina australis), although their relative contributions to catches varied over time. Catch per unit effort has significantly declined for five of the most abundant shark taxa over the study period, increasing only for a single taxon, the sevengill shark (Notorynchus cepedianus). Catches of larger, potentially dangerous white sharks (Carcharodon carcharias) and tiger sharks (Galeocerdo cuvier) saw fewer large animals being caught over time. This pattern was not observed across other taxa. Four different monthly trends were observed in landings of the most abundant eight taxa, reflecting differences in the biology of the catch species. The current study also provides useful information on catches and sizes of grey nurse (Carcharias taurus) and white sharks before and after their protection in NSW waters in 1984 and 1998, respectively. © CSIRO 2011.